WANITA DAN PERANANNYA DALAM MEMAJUKAN UMKM BATIK DI KEBUMEN - azizah, Siti nur (LP2M Institut Teknologi dan Bisnis Asia Malang, 2019)
This study aims to analyze, describe and interpret what factors influence women's empowerment so that it can improve the family's economic welfare. This study is a descriptive study using structured interviews. Subjects were 30 female batik entrepreneurs in Pejagoan and Alian Districts. The results show both women entrepreneurs run businesses to help the family economy and still have little business knowledge, so the local government still has to provide assistance for the progress of the batik industry, especially those owned by women.